2014
DOI: 10.1093/mnras/stu1806
|View full text |Cite
|
Sign up to set email alerts
|

High-velocity blueshifted Fe ii absorption in the dwarf star-forming galaxy PHL 293B: evidence for a wind driven supershell?

Abstract: X-shooter and ISIS WHT spectra of the starforming galaxy PHL 293B also known as A2228-00 and SDSS J223036.79-000636.9 are presented in this paper.We find broad (FWHM = 1000km/s) and very broad (FWZI = 4000km/s) components in the Balmer lines, narrow absorption components in the Balmer series blueshifted by 800km/s, previously undetected FeII multiplet (42) absorptions also blueshifted by 800km/s, IR CaII triplet stellar absorptions consistent with [Fe/H] < −2.0 and no broad components or blushifted absorptions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 63 publications
9
37
1
Order By: Relevance
“…While the observed broad wings in the Balmer lines may have originated in a very old supernova (SN) remnant (the SN rate of PHL 293B is about 3 × 10 −4 yr −1 ), in order to generate relatively narrow absorption profiles such as the ones detected in PHL 293B, it was argued that the absorbing material must cover a substantial fraction of the continuum source, which, in this case, is a young stellar cluster several parsecs in size (Terlevich et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the observed broad wings in the Balmer lines may have originated in a very old supernova (SN) remnant (the SN rate of PHL 293B is about 3 × 10 −4 yr −1 ), in order to generate relatively narrow absorption profiles such as the ones detected in PHL 293B, it was argued that the absorbing material must cover a substantial fraction of the continuum source, which, in this case, is a young stellar cluster several parsecs in size (Terlevich et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…From the observed Balmer line luminosity and using the equivalent width of the Balmer emission lines as an age indicator, the resulting upper limit for the ionizing star cluster mass is M SC ≈ (2-4) × 10 5 M and the upper limit for the age is about (5-7) × 10 6 yr. Terlevich et al (2014) analyzed extensive published and their own photometric and spectroscopic data and found that at the 3σ level, any long-term variability, i.e., over a few years, cannot be larger than 0.02 mag and that any medium term variability, i.e., over a few months, should be less than 0.04 mag. Furthermore, there is no variability at the level of a few tenths of magnitude over a period of 25 yr.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations